A Pathway to a Better Future: Community-Based Tourism for Local Economic Growth in Sayan Village, Ubud - Octaviani, Natasya; Meliana, Magsyanda; Yudhistira, Putu Gde Arie (Politeknik Negeri Bandung, 2023)
Community-Based Tourism (CBT) has become increasingly popular in recent years. This is due to the increasing interest of tourists in traveling more authentically. The CBT concept seeks to create sustainable tourism that positively impacts the local economy. Sayan Tourism Village is one of the Tourism Villages that has implemented the concept. The purpose of this study is to analyze the contribution of CBT in supporting local economic growth in Sayan Tourism Village. The research method used is qualitative research with an exploratory study approach. Data were collected through literature review, observation, and interviews with the Village Government and tourism industry players in Sayan Tourism Village. The results showed that the implementation of CBT in Sayan Tourism Village has had a positive impact on the local economy.